Single-Stage Reconfigurable Solar Converter for Grid-Linked System by using a fuzzy logic (International Journal of Engineering and Computer Science, 2015)
For photovoltaic (PV)-battery application, mostly for utility-scale PV-battery application a new converter i.e. Reconfigurablesolar converter (RSC) is introduce. The output power of PV module varies with solar irradiation; temperature; loads and it quickly andaccurately tracks the sun. The basic concept of the RSC is to employ a single-stage three phase conversion system to perform differentoperation modes such as dc/dc and dc/ac for solar PV systems with energy storage. This converter solution is appealing for PV-batteryapplication as it minimizes the weight, volume, the number of conversion stages there by reducing the cost, and improving efficiency. In thispaper fuzzy logic controller (FLC) is used for controlling the Reconfigurable solar converter (RSC) for photovoltaic (PV)-battery application,mostly for utility-scale PV battery application. The main advantage of fuzzy logic control is to eliminate harmonic content, improve thesystem response and steady state error.